Geographic Information System Application for Water Supply System: A Case Study in Paphos, Cyprus - Hadjimitsis, Diofantos G.; Achilleos, Constantia (My University, 2009)
Geographic Information Systems(GIS) can be successfully introduced as a tool to manage water system infrastructures. This technology was taken into consideration after the local authorities’ estimation for almost 30% losses in the water distribution networks in cities. The major issue of water shortage in the
Keywords: Geographic Information System Application; Water Supply System; Case study; Paphos, Cyprus